Implementasi ERP sebagai Pengintegrasi Sumber Daya Perusahaan pada PT. KSteel Nusantara - Muhammad Naufal Al Hazmi; Raissa Amanda Putri (Teknik Informatika Universitas Pamulang, 2023)
PT KSteel Nusantara is a fabrication company and distributor of building materials which in practice still uses manual recording and has not maximally utilized the development of integrated information technology, especially in the field of sales and warehouse. So that there are several problems such as the length of time recording, prone to data loss and not yet integrated between these two fields. This study aims to implement the Warehouse Management module and the Sales Management module in an integrated information system based on Enterprise Resource Planning (ERP) at PT KSteel Nusantara. In this study using data collection methods that include interviews, literature studies, and observations. Then for system design using a visual modeling method, namely UML (Unified Modeling Language) which contains Use Case Diagrams, Activity Diagrams, Sequence Diagrams and Class Diagrams and uses the Waterfall system development method. The results of the implementation of the Warehouse Management module and the Sales Management module based on Enterprise Resource Planning (ERP) show an increase in operational efficiency through better integration between the sales and warehouse fields, as well as optimization of data management in business processes.